2017
DOI: 10.4158/ep161309.ra
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Cardiovascular Drugs on Glycemic Control: A Review

Abstract: Introduction The prevalence of diabetes is steadily rising in the US, both in the general population and among those with cardiovascular disease (CVD). Understanding how to treat a patient with both conditions is becoming increasingly important. With multiple therapeutic options for CVD management, some medications will invariably impact glycemia in this group of patients. The concept of “DM-friendly” management of CVD is based on a treatment approach of selecting medications that do not impair glycemic contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 79 publications
(90 reference statements)
0
1
0
2
Order By: Relevance
“…During the study period, two DDIs showed a slightly increase, namely antidiabetics and beta-blocking agents and clopidogrel and PPIs. As for the DDI involving antidiabetics and beta-blocking agents, this may provide an example of two drugs deliberately and unavoidably prescribed together [ 33 ]. In the Italian population, beta-blocking agents represent one the most frequently prescribed drug classes, with a prevalence of use of around 25% in patients between 65 and 74 years and an even higher one among those older than 85 years (about 40%) [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…During the study period, two DDIs showed a slightly increase, namely antidiabetics and beta-blocking agents and clopidogrel and PPIs. As for the DDI involving antidiabetics and beta-blocking agents, this may provide an example of two drugs deliberately and unavoidably prescribed together [ 33 ]. In the Italian population, beta-blocking agents represent one the most frequently prescribed drug classes, with a prevalence of use of around 25% in patients between 65 and 74 years and an even higher one among those older than 85 years (about 40%) [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…До недавнього часу основними показаннями до призначення іАПФ були СН, АГ і ЦД, в першу чергу за наявності супутньої АГ або мікроальбумінурії. Ефективність іАПФ у хворих із ХКС із метою вторинної профілактики вивчали в наступних дослідженнях [52,53]: HOPE -пацієнти з ІХС або ЦД і високим ризиком розвитку серцево-судинних ускладнень, але без СН (10 мг/ добу, тривалість 5 років); EUROPA -хворі на ХКС різного за ступенем ризику, без клінічних ознак СН (периндоприл 8 мг/добу, тривалість дослідження -4,2 року); PEACE -пацієнти з ХКС без СН (трандолаприл 2-4 мг/добу, тривалість 4,8 року). НОРЕ і EUROPA продемонстрували зниження серцево-судинного ризику (кардіальна смерть, нефатальний ІМ) на 26 і 20 % відповідно.…”
Section: інгібітори ангіотензинперетворювального ферментуunclassified
“…Огляд літератури /Literature Review/ воджувалося істотним (до 32 %) зменшенням кількості випадків розвитку інсульту [52][53][54].…”
Section: інгібітори ангіотензинперетворювального ферментуunclassified